Production and cytogenetics of tetraploid–octoploid Avena hybrids - Katsiotis, Andreas; Forsberg, R. A. (My University, 1995)
The objectives of this research were to gather hybridization information about crosses between tetraploid and synthetically derived octoploid lines of Avena and their reciprocals, and to study the cytology of the hybrids obtained. When the octoploid plants were used as females, only 2.6% of the pollinated florets set seed, while seed set increased to 39.0% in reciprocal crosses. However, germination was 95.7% for the first group of hybrids and only 18.2% for the reciprocals. These diverse results can be explained by the paternal: maternal endosperm genomic ratios and the hypothesis of polar nuclei activation. The tetraploid‐octoploid hybrids did not always contain 42 chromosomes. Octoploid lines derived indirectly from tetraploid (AABB) × hexaploid (AACCDD) crosses were found to retain their A and B genome chromosomes. Univalents in the above hybrids averaged 15.44 in 1990 and 15.15 in 1991, indicating the presence of C and D genome chromosomes inherited from the octoploid lines. Directly synthesized octoploids from diploid (A c A c ) × hexaploid (AACCDD) crosses were found to form 20.44 univalents, 5.30 bivalents, and 2.69 trivalents when crossed with AABB tetraploid species. The high number of univalents indicates that chromosomes from at least three genomes, i.e. B, C, and D, remain unpaired, while trivalents are the result of homology between the A and A c genomes. Hybrids between tetraploid and octoploid lines can be obtained at low frequencies but, regardless of the direction of the cross, these hybrids are highly sterile.
Keywords: Activation index; Avena species; Endosperm; Interspecific hybrids; Oat genomes